PENGARUH TINGKAT KESEHATAN BANK TERHADAP PERTUMBUHAN LABA DENGAN METODE RGEC PADA BANK PEMBANGUNAN DAERAH DI INDONESIA TAHUN 2017-2019 - Yongky Rangga Yuda Nugraha; Diah Ayu Fitriyani; Agus Salim; M. Atep Effiana Taufik; Willy Nurhayadi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Profit growth is one measure of a banks success in meeting the banks health levels.The purpose of this study is to partially and simultaneously determine the effect ofrisk profile (NPL), good corporate governance (GCG), earnings (ROA), andcapital (CAR) on profit growth at Regional Development Banks in Indonesia in2017 - 2019. The method used in this research is quantitative method, while thetype of data is secondary data. The data analysis technique used is the classicalassumption test, multiple regression test, hypothesis test, and determinationcoefficient test.The results of this study found that partially the risk profile has noeffect on profit growth. Partially the GCG has no effect on profit growth. Partiallythe earnings affects profit growth. Partially the capital has no effect on profitgrowth. While simultaneously the risk profile, GCG, earnings, and capital have aneffect on profit growth